2011
DOI: 10.1007/s12010-011-9369-x
|View full text |Cite
|
Sign up to set email alerts
|

Production of Cyclodextrins from Cornstarch Granules in a Sequential Batch Mode and in the Presence of Ethanol

Abstract: The influence of Toruzyme® cyclomaltodextrin glucanotransferase concentration and the presence of ethanol have been studied for the production of α-, β-, and γ-cyclodextrins (CDs) from 15% (w/v) cornstarch, at 65 °C and pH 6, with the aim of increasing CD yield. The selected concentrations for a single batch reactor were 10% (v/v) ethanol and 0.1% (v/v) enzyme, yielding after 12 h, 37% total CDs, of which 52.2% was α-CD, 38.8% β-CD, and 9.0% γ-CD. The enzyme specific activities per unit mass of protein for pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…When considering the CM, ethanol was not an efficient reagent, decreasing the CD production (α, β, and γ‐CD) and the conversion rate ( p < 0.05). Ethanol was used to improve the production of CDs, as several studies reported an increase in the production of these components with the use of this reagent . The improvement observed with ethanol addition and CB increases the interest in the use of the CB substrate (now discarded in the cassava starch industries) for CD production.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…When considering the CM, ethanol was not an efficient reagent, decreasing the CD production (α, β, and γ‐CD) and the conversion rate ( p < 0.05). Ethanol was used to improve the production of CDs, as several studies reported an increase in the production of these components with the use of this reagent . The improvement observed with ethanol addition and CB increases the interest in the use of the CB substrate (now discarded in the cassava starch industries) for CD production.…”
Section: Resultsmentioning
confidence: 99%
“…Ethanol possible promotes changes in both the hydration and infrastructure of the enzyme (for example, displacement of water molecules by the solvent either on the surface of the protein or in the active site region). The polar groups contained in the solvent may make direct molecular effects on biocatalyst activity …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations